2021
DOI: 10.1002/ieam.4548
|View full text |Cite
|
Sign up to set email alerts
|

Moving persistence assessments into the 21st century: A role for weight‐of‐evidence and overall persistence

Abstract: Assessing the persistence of chemicals in the environment is a key element in existing regulatory frameworks to protect human health and ecosystems. Persistence in the environment depends on many fate processes, including abiotic and biotic transformations and physical partitioning, which depend on substances' physicochemical properties and environmental conditions. A main challenge in persistence assessment is that existing frameworks rely on simplistic and reductionist evaluation schemes that may lead substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 127 publications
0
16
0
Order By: Relevance
“…Our system was constructed with conventional, ensemble, and deep learning algorithms on the basis of a large dataset, showing excellent interpretability, broad ADs, good generalization capability, and high accuracy, especially in the prediction of false-negative substances. We expected that the screening system is not only limited to the current algorithms and database but it also can better serve with the adoption of the integrated assessment framework of persistence, 52 uniform toxicity data that can be retrieved from various exposure scenarios, and more chemicals with more enriched data, including ionic organic compounds, properties with balanced numbers of substances, 3D chemical structure images using Graph Neural Networks, as well as realtime modeling features for updating chemical information. Our research contributes to the management of PMT/vPvM substances over the complete life cycle, particularly in China, with its size of chemical industry larger than the EU and U.S. combined.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Our system was constructed with conventional, ensemble, and deep learning algorithms on the basis of a large dataset, showing excellent interpretability, broad ADs, good generalization capability, and high accuracy, especially in the prediction of false-negative substances. We expected that the screening system is not only limited to the current algorithms and database but it also can better serve with the adoption of the integrated assessment framework of persistence, 52 uniform toxicity data that can be retrieved from various exposure scenarios, and more chemicals with more enriched data, including ionic organic compounds, properties with balanced numbers of substances, 3D chemical structure images using Graph Neural Networks, as well as realtime modeling features for updating chemical information. Our research contributes to the management of PMT/vPvM substances over the complete life cycle, particularly in China, with its size of chemical industry larger than the EU and U.S. combined.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Not allowing for weight-of-evidence conclusions would expand the number of "Potential P/vP" and "insufficient data" conclusions while decreasing the number of "Not P" and P/vP conclusions. If one were to introduce an alternative persistency threshold instead of media specific half-lives, like the emission scenario dependent multimedia parameter P ov , 155 this would either severely restrict the number of substances considered P/vP if intense data requirements are needed, or would have an unknown impact if low data quality modeling threshold values are introduced as weight-of-evidence. If the readily/inherent biodegradability tests were used as the threshold for P, the Potential PMT/vPvM substances would become PM, PMT, or vPvM.…”
Section: Distribution Of Pmt/vpvm Hazard Assessmentsmentioning
confidence: 99%
“…McLachlan and colleagues further extended this idea, suggesting that all laboratory tests could include a reference benchmark chemical substance against which the relative biodegradation (extent or rate) of test chemical substances could be measured (McLachlan et al, 2017), a concept that they termed benchmarking (Table 3). They further demonstrated how the concept could be used to separate degradation half‐lives from dissipation processes in the field (a lake system; see Redman et al, 2021) and outlined its use more generally in chemical hazard and risk assessments, in particular, in calibrating and translating laboratory to field data. More recently, the same group demonstrated that comparable half‐life determinations between field‐derived and OECD TG 309 simulation tests were obtained if the tests were not spiked with a given test substance, but where biodegradation of substances in the natural waters was followed by targeted (Li & McLachlan, 2019) or nontargeted chemical analyses (Li & McLachlan, 2020).…”
Section: Current and Future Options In Persistence Assessmentmentioning
confidence: 99%